Role of folic acid supplementation in level of c-reactive protein in metabolic syndrome : evidence based case report - Sjarkowi, Anissa Syafitri; Wulandari, Yohannessa; Trismiyanti, Trismiyanti (Indonesian Nutrition Association, 2024)
Introduction: The prevalence of metabolic syndrome is increasing, its progression involves an inflammatory response that has an important impact on the initiation, progressivity, and complications of several diseases such as heart disease, stroke, type 2 diabetes mellitus, and cancer. C-reactive protein (CRP) is one of the inflammation markers increased in patients with metabolic syndrome. Folic acid has a role in metabolizing homocysteine and improving endothelial function. There have been many studies conducted, but the results are still inconsistent. Method: Literature searching was conducted using PubMed, Cochrane Library, and Embase databases. MeSH terms, advanced search and eligibility criteria were used for title/abstract screening before journal review. Results: One systematic review and meta-analysis (SR-MA) and one RCT met the PICO and eligibility criteria. The SR-MA found that folic acid administration can reduce CRP level (WMD -0.94 (95% CI -1.56 – 0.32; p=0.00) at a dose of 0.15 mg/day for 12 weeks to 10 mg/day for 2 weeks, while the RCT found an insignificant result. Conclusion: Folic acid supplementation has a potential benefit to decrease CRP levels in metabolic syndrome.